DESAIN BAHAN AJAR PENJUMLAHAN PECAHAN BERBASISPENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK SISWA KELAS IV SEKOLAH DASAR NEGERI 23 INDRALAYA - Ullya; Zulkardi; Putri, Ratu Ilma Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2010)
This research purposes to result teaching material of fractional summation on Indonesia Realistic Mathematic Education (PMRI) basis for class IV of SD N 23 Indralaya and find out dtudent‟s in enumerating fractional trough activity from informal to formal. The research subject of class IV SD N 23 Indralaya. Researcher used the methods: Design research ( Gravemaije, 2009) designed in 3 stages, i.e. Front – end analysis and expert review, teaching expriment and reflection, and assessment and evaluation stage. Based on front- end analysis, teaching material design on PMRI basis in the from of student book and teacher‟,s. Stage was teaching experiment carried out in class IV and observerped by 4 (four) observers, 3 obsevers observed studens aktivity and 1 (one) obsever which wasthe researcher erself observer the students and teacher activities, the result (after analyzed) was indicator 1 with the best category, indicator number 2, 3,4,5, 6, 7, and 8 student activity were seen well category, while in indecator numser 9 with poor criteria. Menwhile in the third stage was assessment or evaluatin was carried out to refer the students learning result achievement either daily evaluation or assignments. For daily evaluation result was 97,96% achievement in summsting the efrction with simelar quotation, 85,71% different quotation 65,21% student,s achiefement in summating mixed fraction and 83,67% student,s achievement in summating defferent quotation fraction with mixed mix praction.The student‟s assignment result for the first student who reached ≥ KKM was 33 students (67,30%), second assignment achievement was 38 students (77,66%), the third assignment achievement was 40 students (81,63%), and the fourth assignment reached 41 students (83,67%) which generally the assignment result was increasing. DOI: 10.22342/jpm.4.2.818